Development of ODL in a Newly Industrialized Country according to Face-to-Face Contact, ICT, and E-Readiness - van Zyl, J. Marinda; Els, Christoffel Johannes; Blignaut, Anita Seugnet (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2013)
A large number of unqualified and under-qualified in-service teachers are holding back socio-economical development in South Africa, a newly industrialized country. Open and distance learning (ODL) provides an innovative strategy and praxis for developing and newly industrialized countries to reach their educational and socio-economical objectives through professional development and training. In order to examine factors which affect the success of ODL offered by the North-West University in South Africa, a qualitative and quantitative research approach is used. Factors examined include face-to-face classroom contact, the implementation and use of ICTs, and e-readiness. The relationships between these factors are also discussed. A questionnaire was administered to 87 teacher-students in four Advanced Certificate in Education (ACE) programs to collect quantitative data regarding aspects of their classes and the e-readiness of students. This data was qualitatively elaborated upon by three semi-structured, open-ended focus-group interviews. Besides descriptive statistics, Spearman’s rank-order correlations (r) were determined between variables pertaining to negative feelings towards face-to-face classroom contact, ODL as students’ choice of delivery mode, and students’ positive attitude towards information and communication technology (ICT). Combined quantitative and qualitative findings were used to evaluate the effectiveness of contact classes as well as the e-readiness of students towards the attainment of ODL development Phase D. This phase refers to UNESCO’s description of ICT implementation, integration, and use. Relationships (Spearman’s rank-order correlations) between ODL, as teacher-students’ choice of educational delivery mode, and aspects of their e-readiness suggest that the e-readiness of teacher-students is implicit to their choice of ODL as educational delivery mode for professional development.